2000
DOI: 10.1128/iai.68.12.6954-6961.2000
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathologic Effects of Tumor Necrosis Factor Alpha in Murine Mycobacterial Infection Are Dose Dependent

Abstract: In experimental mycobacterial infection, tumor necrosis factor alpha (TNF-␣) is required for control of bacillary growth and the protective granulomatous response, but may cause immunopathology. To directly examine the positive and detrimental effects of this cytokine, a murine model was used in which different amounts of TNF-␣ were delivered to the site of infection. Mice with a disruption in the TNF-␣ gene (TNF-KO) or wild-type mice were infected with low or high doses of recombinant Mycobacterium bovis BCG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
127
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 32 publications
9
127
1
Order By: Relevance
“…However, when TNF-␣ was added back by infection with BCG-TNF, the replication of the infecting organisms was reduced and the number of viable bacteria was decreased. This was also noted in vivo: when TNF-KO mice were infected with recombinant BCG-TNF, the number of infecting BCG-TNF was reduced whereas BCG-vector grew in all organs tested (24). Similarly, in human macrophages infected in vitro with M. tuberculosis, it has been shown that when TNF-␣ is added, the cells are more efficient at curbing the growth of the bacilli than when other cytokines or cytokine combinations, including IFN-␥, are added (3).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, when TNF-␣ was added back by infection with BCG-TNF, the replication of the infecting organisms was reduced and the number of viable bacteria was decreased. This was also noted in vivo: when TNF-KO mice were infected with recombinant BCG-TNF, the number of infecting BCG-TNF was reduced whereas BCG-vector grew in all organs tested (24). Similarly, in human macrophages infected in vitro with M. tuberculosis, it has been shown that when TNF-␣ is added, the cells are more efficient at curbing the growth of the bacilli than when other cytokines or cytokine combinations, including IFN-␥, are added (3).…”
Section: Discussionmentioning
confidence: 80%
“…However, the enzyme appeared to be inactive, since nitrite was not detected in the culture supernatant of infected cells, and the intracellular mycobacteria were not killed. Similarly, iNOS protein has been shown to be expressed in the macrophages of mycobacteria-infected TNF-␣ receptor gene-disrupted mice (TNFR-KO) (1) and TNF-KO mice (2,24), even in the absence of TNF-␣ or TNF-␣ signaling. However, since the infection was not controlled in all of these in vivo studies, either the enzyme was not active or it was not activated efficiently enough or early enough.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α controls MTBC infection progression to disease as evidenced by the increase incidence of active TB in patients treated with anti-TNF-α [26,27]. However, its protective role appears to be dose dependent with increased levels promoting immunopathology [28,29]. IL-2 also is important in the host by stimulating the proliferation and differentiation of T cells and NK cells for increased effectiveness in MTBC elimination.…”
Section: Discussionmentioning
confidence: 99%
“…13 The partial protection generated in mem-TNF mice could indicate local cell-to-cell TNF signaling by membrane-expressed TNF on T cells or macrophages at the site of infection, leading to a partial activation of the immune cells. Indeed, for the resistance to intracellular pathogens TNF must be produced locally, 36 whereas exogenous systemically administered TNF is ineffective. 37 Several biological functions of membrane TNF signaling through both TNFR1 and TNFR2 have been reported previously in vitro 9 and in vivo using transgenic mice expressing membrane TNF.…”
Section: Discussionmentioning
confidence: 99%